Krisis ekonomi: Penyebab implikasi dan prospeknya di masa depan - Anwar Nasution (Economic Journal of Emerging Markets, 1997)
The financial crisis occurred in many of Asian countries was a shocking phenomena. These countries which known had a miracle economic performance were likely ^gille atached by financial crisis tremendously. This paper focus on the cause, implication and prospect of the crisis to Indonesia economic. Despite the crisis caused by a combination of multi-factors, both of external and internal, it has been an evidence of inconsistency between foreign exchange and fiscal- monetary policy. The crisis has been a real test of their economic fundamental. Apparently, this crisis will has caused serious problem to their economic, both in short term and long term. Hence, the exfefence of a comprehensive, essential and consistent policy is needed urgently. Today is right momentum to improve Indonesian economic seriously.